2008
DOI: 10.1152/japplphysiol.00582.2007
|View full text |Cite
|
Sign up to set email alerts
|

Single-breath test in lateral decubitus reflects function of single lungs grafted for interstitial lung disease

Abstract: After single-lung transplantation (SLT) for emphysema, heterogeneity of ventilation distribution in the graft can be assessed by measuring the slope of the alveolar plateau, computed from a single-breath test, performed in lateral decubitus with this lung in the nondependent position. We tested the validity of this technique in patients with SLT for interstitial lung diseases (ILD). Twelve patients with SLT for ILD, 12 nontransplanted patients with ILD, and 10 healthy control subjects performed single-breath w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Two recent studies in recipients of SLT for emphysema or fibrosis suggested that when performed in lateral decubitus, the single-breath test may also provide information on ventilation distribution in the graft in this patient population. 85,86 Exhaled gases Exhaled nitric oxide (eNO) is a well-recognized biomarker of airway inflammation. In stable lung transplant recipients and patients with BOS, eNO reflects the expression of bronchial epithelial inducible NO synthase and positively correlates with airway neutrophilia.…”
Section: Distribution Of Ventilationmentioning
confidence: 99%
“…Two recent studies in recipients of SLT for emphysema or fibrosis suggested that when performed in lateral decubitus, the single-breath test may also provide information on ventilation distribution in the graft in this patient population. 85,86 Exhaled gases Exhaled nitric oxide (eNO) is a well-recognized biomarker of airway inflammation. In stable lung transplant recipients and patients with BOS, eNO reflects the expression of bronchial epithelial inducible NO synthase and positively correlates with airway neutrophilia.…”
Section: Distribution Of Ventilationmentioning
confidence: 99%